INFLUENCE CELEBRITY ENDORSEMENT AND HALAL PRODUCT IMAGE ON BRAND LOYALTY OF HANASUI COSMETICS IN LHOKSEUMAWE CITY - Khairina AR; Teuku Zulkarnaen; Munandar; Zahara Husna (RADJA PUBLIKA, 2024)
This study was conducted to examine the effect of celebrity endorsement and halal product image on Hanasui cosmetic brand loyalty in Lhokseumawe City. The population in this study were women over 18 years of age who had used Hanasui products. While the number of samples in this study were 96 respondents using non-probability sampling technique, namely purposive sampling. The data used in this study are primary data obtained by distributing questionnaires. The data analysis method used is multiple linear regression analysis techniques using SPSS 25. Data analysis uses the classical assumption test, partial test (t), simultaneous test (f) and the coefficient of determination test. The results showed that celebrity endorsement and halal product image had a positive and significant effect on Hanasui cosmetic brand loyalty in Lhokseumawe City.